Pengaruh Pemikiran Ibnu Khaldun terhadap Perkembangan Ekonomi Islam di Indonesia - Adelia Gusfira; Azza Bunaia; Valina Sinka; Ahmad Wahyudi Zein (Moral : Jurnal kajian Pendidikan Islam, 2024)
This article discusses the influence of Ibnu Khaldun's thoughts on economic development in Indonesia, focusing on the theories put forward by a great thinker of the 14th century in the context of modern Indonesian economics, namely Ibnu Khaldun, in his monumental work Muqaddimah, introducing concepts such as cycles. civilization, the importance of social and cultural factors in economic development, and the role of the state in regulating the economy. Through this study, it is revealed how these concepts can provide insight into understanding the dynamics of the Indonesian economy, which is often influenced by complex external and internal factors. By analyzing Indonesia's economic development from the colonial period to post-independence, this research shows that Ibnu Khaldun's thoughts, even though they come from a very different historical context, are still relevant in explaining economic inequality, the role of bureaucracy, and the relationship between the state and the market in Indonesia. It is hoped that this research can provide a new perspective in efforts to understand and overcome the economic challenges faced by developing countries like Indonesia.